2018
DOI: 10.1177/1753944718792428
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection in on-pump coronary artery bypass grafting surgery: analysis of the effectiveness of the use of retrograde Celsior®

Abstract: An isolated single dose of retrograde Celsior® may be an effective and safe myocardial protection strategy in on-pump CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The eleven studies 6,8‐11,13‐18 included in the analysis had an aggregate of 5684 participants, 2681 of whom were microplegia patients versus 3003 who received other types of cardioplegia. The characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The eleven studies 6,8‐11,13‐18 included in the analysis had an aggregate of 5684 participants, 2681 of whom were microplegia patients versus 3003 who received other types of cardioplegia. The characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The exceptions were Koechlin et al 18 and Onorati 16 where volumes were not reported. In the two trials by Lopez Menendez et al, 13,14 the volume of crystalloids in the microplegia was not given but reported to be “minimal.” In Menasche et al 8 the volume of diluted cardioplegia was 1000 mL compared to 58 ± 14 mL ( P = .0001), whilst in Albacker et al 17 the volume of crystalloids in the diluted cardioplegia was 740 CC (95% CI: 690‐794) compared to 65 CC (95% CI: 62‐67) ( P < .01). Four trials involving 196 patients reported the volume of crystalloids in mL used in the cardioplegia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations